ANALISIS TINGKAT KETIMPANGAN PEMBANGUNAN DAN PERTUMBUHAN EKONOMI KABUPATEN / KOTA DI KALIMANTAN BARAT TAHUN 2010 - 2013 - B01108038, NURUL FUAD B01108038 FUAD (Jurnal Pembangunan dan Pemerataan, 2015)
AbstractThis study aims to prove whether the Kuznets hypothesis applies in West Kalimantan usedTheil index and GDP per capita, as well as used SPSS through correlation Pearson to find out howstrong the relationship between the variables of economic growth and GDP per capita on the level ofdevelopment gaps Regency / City in West Kalimantan in the period 2010 to 2013. From this analysisit was found that hypothesis Kuznets not apply in West Kalimantan, this is because the value of indexTheil is quite high and the fluctuation while the strength of the relationship between variables wasfound that the variable index of inequality and GDP per capita positive value of 0.934 and therelationship between the index variable inequality and variable economic growth is also positivevalue of 0.118 which means that any increase will be followed peningkaran variable other variables.Keywords: Inequality Regional Development, Theil Index, Kuznets Hypothesis, GDP percapita, Economic Growth, Pearson Correlation Analysis